Modeling and Analyzing the Power Consumption in Query Processing For Distributed Database - Teh , Pey Si (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Green computing has been generally practiced in almost all kind of fields especially in the recent years as environmental sustainability is getting more important. High power consumption increases the carbon emission which is adverse to the environment. This project focuses on applying green computing in query processing specifically for distributed database in healthcare industry. The information about a patient is stored in the database of the hospital the patient visited. However, currently this information is not being shared among hospitals which are crucial for diagnosis purpose. Hence, the objective of this project is to model the process of data retrieval from database distributed at different hospitals by using different query processing strategies and analyzes the energy consumption to access data from these distributed databases. Two strategies are used to retrieve the distributed data during simulation which are complete replication and horizontal fragmentation. Based on the analyzed result from the simulation, the identified energy-efficient strategy is complete replication which consumed lower power consumption by enabling local access to data stored in distributed database.